ANALISIS LEVEL BERFIKIR MAHASISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG CAMPURAN BILANGAN BULAT DENGAN MENGGUNAKAN TAKSONOMI BLOOM - Sefriani, Adelia Alin Sefriani; Darmawan, Puguh (Politeknik Negeri Jakarta, 2024)
This study aims to analyze students' cognitive abilities in solving mixed integer arithmetic operations based on Bloom's Taxonomy. A qualitative descriptive method was employed, involving three students from mathematics education and mathematics study programs. The research instruments included written tests and structured interviews designed to measure six cognitive levels: Knowledge, Understanding, Application, Analysis, Synthesis, and Evaluation. The results revealed variations in students' cognitive abilities. Student PI was at the low level, demonstrating proficiency in Knowledge and Understanding but struggling with Analysis, Synthesis, and Evaluation. Student JW was at the intermediate level, with adequate skills in Analysis but limited performance in Synthesis and Evaluation. Student AA was at the high level, successfully completing tasks up to Evaluation, although showing limitations in Synthesis complexity. This study highlights the significance of applying Bloom's Taxonomy to evaluate students' cognitive abilities. The findings provide insights into teaching strategies to enhance students' understanding and skills in solving mixed integer arithmetic operations.